Consuming literature : best sellers and the commercialization of literary production in contemporary China - Kong, Shuyu (Stanford University Press, 2005)
Shuyu Kong examines the changes taking place in literary writing & publishing in contemporary China under the influence of the emerging market economy. The author focuses on the revival of literary best sellers in the Chinese book market & the establishment of a best-seller production machine.